2020
DOI: 10.1021/acs.jchemed.0c00367
|View full text |Cite
|
Sign up to set email alerts
|

Demonstrating Real-World Applications of Chemistry in Customs Laboratories Facilitating Global Trade and Regulation by Guiding Students through Organoleptic Assessment of Olive Oil Using Their Senses of Taste and Smell

Abstract: Recently, the customs chemistry laboratory of Bari, Italy, initiated a project to organize activities for students, with the purpose of promoting awareness of its role and services in the Apulia region, as well as to encourage students to study chemistry. This paper aims to show how the project can be an effective way to introduce students to the role of chemical analysis in the evaluation and valorization of one of the more-exported Italian products, by means of a 2 h lab-integrated lecture. Extra virgin oliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…To be able to describe the product taste and assess customer acceptance is beneficial to marketing. In fact, it had the same weight as instrumental analysis. , In this project, typical evaluation started with observation of the appearance followed by smelling and tasting of samples. The evaluators sucked up the wine and taste it with the wine over their tongues.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To be able to describe the product taste and assess customer acceptance is beneficial to marketing. In fact, it had the same weight as instrumental analysis. , In this project, typical evaluation started with observation of the appearance followed by smelling and tasting of samples. The evaluators sucked up the wine and taste it with the wine over their tongues.…”
Section: Resultsmentioning
confidence: 99%
“…After the evaluation process, the evaluators scored the wine on the basis of their personal opinions. The evaluation activities helped the students to understand the link between senses and organoleptic analysis, as well as recognized the need for objectivity in analysis, even though it may seem subjective, because the exercise relied on people’s sense and aptitude . Besides, a new method of quantitative description analysis was introduced to the students to generate a flavor profile.…”
Section: Resultsmentioning
confidence: 99%
“…A key part of the project is the handson activity, since laboratorial activities need to have a high level of active participation in all steps, from the planning to the putting into practice, as also reported in other cases. 7,18,66 The only limitation of this project and in general of this educational approach is that it needs much more time than normal lessons, and it require a very good preparation by the teachers, who need to visit the museum in advance, prepare the materials and dedicate extra-curricular hours to let students work to their project. In the case study reported in this paper, it is important to underline that the undergraduate students who participated were able to explore some scientific concepts, such as the temperature, the temperature-dependence of density, the miscibility among liquids, the density as chemical-physical property of a chemical substance, by using non-formal educational methodologies starting from the investigation of the history of some objects collected in the science museum.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…The project flowchart shown in Figure starts with laboratory experiments, in which classical methods (such as determination of free acidity and number of peroxides) and instrumental analytical techniques (UV–vis spectroscopic analysis to determine K232 and K270 index and gas-chromatographic analysis) were applied to different commercial and fresh EVOO samples . Olive oil is a very good food matrix to improve students’ analytical skills because it gives the possibility to apply standard analytical techniques, practiced in the previous school years, to a real sample with a relatively high level of complexity. This opens the possibility to explore several basic chemical concepts, such as the physical chemistry of water/oil systems, principles of separation techniques, such as the extraction of single classes of chemical compounds from complex matrix, and how to treat a real sample before performing a chemical analysis and so on.…”
Section: Projects On Extra-virgin Olive Oil With High School and Unde...mentioning
confidence: 99%
“…On the analytical point of view, this spectroscopic method has been validated, , and its ability to quantify main pigments in extra-virgin olive oils has been compared with standard techniques, such as high-performance liquid chromatography (HPLC), showing its robustness and reliability for fast analysis of olive oils. From the educational point of view, the theme of olive oils and in general vegetable oils has several advantages, since it allows teachers to explore different aspects of chemistry, such as food chemistry, natural compounds, and the healthy and nutraceutical properties of olive oils. Olive oil chemistry is indeed an interesting topic due to several educational implications. It can be used to discuss and compare different analytical methods for the chemical characterization of a complex matrix, to describe the saponification reaction, and to show some applications about sustainability in chemistry, such as the conversion of vegetable and plant oils into biodiesels. , …”
Section: Introductionmentioning
confidence: 99%